2006
DOI: 10.1007/s10600-006-0102-x
|View full text |Cite
|
Sign up to set email alerts
|

Component composition of essential oils from four species of the genus Achillea growing in Kazakhstan

Abstract: The component composition of the four species Achillea filipendulina, A. sudetica, A. ledebourii, and A. cartilaginea was studied by GC-MS. It was found that the principal components of the essential oil (%) were santolina alcohol (29.1) and borneol (27.9) for A. filipendulina, linalool (11.8) and caryophyllene (8.9) for A. sudetica, germacrene D (20.55) for A. ledebourii, and α-thujone (26.15) and β-thujone (11.76) for A. cartilaginea. The chemical composition of the essential oils from A. sudetica, A. ledebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
(14 reference statements)
0
4
0
1
Order By: Relevance
“…For instance, the essential oil of A. filipendulina collected from Tehran were mostly composed of limonene (26.7 %), carvacrol (9.3 %), 1,8‐cineole (8.7 %), borneol (7.8 %), and α ‐humulene (5.6 %) . In another study, the essential oil obtained from A. filipendulina collected from Kazakhstan was shown to mainly composed of santolina alcohol (29.0 %), borneol (27.8 %), 1,8‐cineole (19.1 %), and bornyl acetate (8.1 %) . Mosayebi et al .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…For instance, the essential oil of A. filipendulina collected from Tehran were mostly composed of limonene (26.7 %), carvacrol (9.3 %), 1,8‐cineole (8.7 %), borneol (7.8 %), and α ‐humulene (5.6 %) . In another study, the essential oil obtained from A. filipendulina collected from Kazakhstan was shown to mainly composed of santolina alcohol (29.0 %), borneol (27.8 %), 1,8‐cineole (19.1 %), and bornyl acetate (8.1 %) . Mosayebi et al .…”
Section: Resultsmentioning
confidence: 98%
“…There are also some components such as cis ‐chrysanthenyl acetate that is only present in the stem of this plant. Moreover, there are almost no major components present in all three segments of the plant . Several studies have shown that santolina alcohol, carvacrol, 1,8‐cineole, and borneol exhibited antimicrobial activates against bacteria, with two latter also demonstrating synergistic effects .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…В литературе имеются данные об исследовании компонентного состава эфирного масла, флавоноидов, сесквитерпеновых лактонов тысячелистника обыкновенного (A. millefolium) и др. [2][3][4][5][6][7][8], об активности этанольного экстракта корней тысячелистника благородного (A. nobilis L.) против эпилепсии и антимикробной активности эфирного масла A. eriophora [9,10].…”
Section: Introductionunclassified
“…Oxygenated nerolidol derivatives are not typical for Achillea essential oils. To the best of our knowledge, there are only two reports concerning the presence of cabrueva oxides, in A. eriophora [17] and A. sudetica [18]. Cabreuva oxides, isohumbertiols and bejarol were previously found in Tanacetum fruticulosum essential oil [19], Santolina oblongifolia oil [20], cabreuva oil [21] and vassoura oil [22,23].…”
mentioning
confidence: 95%